Spiritualitas Kenosis: Sebuah Alternatif bagi Problematika Fenomena Narsisisme - Purnomo, Wimbodo (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2016)
Modernity is like a double-edged sword; it produces positive and negative poles. The positive pole of modernity is accepted, but the negative pole brings more worries to humanity. One of some negative effects of modernity is the culture of narcissism. It attacks the ultimate principles in human’s life; therefore we can say that personal, cultural, and spiritual problems are narcissistic problems. The writer argues that narcissism has become epidemic which has beem slowly infecting people accross the globe. It has threatened humanity. Thus, science, ethics, philosophy and, even, theology cannot just stay quietly in their comfort zones. Humanity has to be saved and that path of salvation has to be placed in the most personal point. That is the ‘self’. To save humanity means to return to the Most Divine as the “True Self”. It indicates the fusion between the Most Divine and I. It is expected from the fusion that human will have the paradigm of the Most Divine, including in emptying the self.